A hybrid therapeutic approach for decreasing postoperative complications in patients with adult lumbar degenerative scoliosis. Issue 30 (24th July 2020) - Zhao, Yongfei; Liang, Yan; Wang, Tianhao; Wang, Zheng; Lu, Ning
Abstract : Abstract: To decrease postoperative complications in patients with adult lumbar degenerative scoliosis (ALDS), short-segment fusion surgery was used in this study. However, the incidence of adjacent segment disease was found to be remarkable. Therefore, we applied the hybrid treatment (short-segment fusion for responsibility levels plus nonfusion stabilization of lumbar segments, which was called the Wallis system, for the proximal level) to patients enrolled into this study. The purpose of this study was to investigate the feasibility of a novel hybrid therapeutic approach for treating patients with ALDS. From January 2011 to January 2017, a retrospective study was conducted consisting of 16 patients with ALDS who were treated with hybrid treatment. All patients were treated with short-segment decompression and fusion for responsibility levels and nonfusion stabilization of lumbar segments for the proximal levels. The imaging outcomes were evaluated preoperatively and at the time of follow-up. The mean visual analog score for back pain decreased from 6.1 ± 2.0 preoperatively to 2.1 ± 0.7 at 2-year follow-up ( P  < .05), and the mean visual analog score for leg pain reduced from 8.1 ± 0.6 preoperatively to 1.3 ± 0.8 at 2-year follow-up ( P  < .05). The Oswestry disability index scores improved from 65.4 ± 16.3% preoperatively to 18.3 ± 5.6% at 2-year follow-up ( P  < .05). The mean Cobb angle was 22.1 ± 6.2° preoperatively, and 13.8 ± 6.8° at 2-year follow-up ( P  < .05). The lumbar lordosis changed from −40.4 ± 14.8° to −43.5 ± 11.2° at 2-year follow-up ( P  < .05). Solid fusion was achieved in all the patients, and no incidence of adjacent segment disease was noted as well. The proposed hybrid treatment for patients with ALDS can achieve favorable clinical outcomes and a lower incidence of ALDS. However, the correction of deformity is still limited that highlights the necessity of further study.